Baicalin induces apoptosis and autophagy in resistant human hepatocellular carcinoma cell line Bel-7402/5-FU cells via PI3K/AKT pathway - Fei Li; Zilin Lan; Weiwei Jiang; Jianheng Zhou; Jiumao Lin; Jinyan Zhao (Journal of Holistic Integrative Pharmacy)
Objective: Multidrug resistance (MDR) is one main cause of chemotherapy failure. Baicalin is an important active ingredient with anticancer potential in many Chinese herbal medicines. In order to understand the function of baicalin reversing MDR in hepatocellular carcinoma (HCC) and the molecular mechanisms that underlie it, the current study was designed. Methods: Bel-7402 and Bel-7402/5-FU cells were cultured, and MTT assay was applied to detect cell viability and the cross-resistance of Bel-7402/5-FU cells. The pump function, apoptosis, and autophagy were detected by flow cytometry. The related proteins were detected by Western blot assay. The PI3K agonist (740Y-P) was used to verify whether baicalin overcomes the drug resistance of HCC cells by blocking the PI3K/AKT pathway. Results: The findings showed that Bel-7402/5-FU cells were cross-resistant to different chemotherapeutic drugs. Baicalin inhibited cell viability in both Bel-7402/5-FU and Bel-7402 ​cells, and baicalin increased sensitivity of Bel-7402/5-FU cells to 5-FU in time- and dose-dependent manners. Baicalin increased the accumulation of doxorubicin and rhodamine-123 in Bel-7402/5-FU cells and inhibited the protein expression of ABCG2, ABCB1, and ABCC1, associated with pump function. In addition, baicalin induced apoptosis of Bel-7402/5-FU cells via up-regulating Bax expression. Furthermore, baicalin increased autophagy through regulating LC3-Ⅱ, p62, and Beclin-1. Baicalin reversed drug resistance in Bel-7402/5-FU cells by inhibiting the PI3K/AKT pathway, which promoted autophagy and apoptosis to restore chemosensitivity. Conclusion: Baicalin increased accumulation of chemotherapy drugs and induced apoptosis and autophagy in Bel-7402/5-FU cells by inhibiting the PI3K/AKT signaling pathway, that may be the important mechanism by which baicalin reverses the MDR of HCC.